Use of dandelion root in functional bread technology - A. P. Korolev; O. V. Feofilaktova; N. V. Zavorokhina; A. V. Tarasov (Новые технологии)
Prevention of nutritional diseases with the help of functional foods remains relevant. Therefore, the development of food technology using raw materials that contribute to the formation of functional properties is relevant and has scientific and practical significance. The object of the research was every day product, i.e. bread made from premium wheat flour. In order to form functional properties non-traditional plant raw materials were used to enrich bread – dandelion root, characterized by a high content of prebiotic substance – inulin. The purpose of the research was to substantiate the creation of bakery products for a wide range of consumers, enriched with wild plant materials with functional properties. Organoleptic evaluation was carried out in accordance with GOST R 53161-2008; dietary fiber content according to GOST R 54014-2010; vitamins according to the General Pharmacopoeia. 1.2.3.0017.15. As a result of laboratory baking, experimental samples of bread were obtained from premium wheat flour containing dandelion root powder in the recipe in amounts of 5, 10 and 15%. An organoleptic assessment of the quality of the prototypes made it possible to justify the choice of a bread recipe made from wheat flour with the addition of dandelion root powder in an amount of 5%. A larger amount contributed to the appearance of a bitter taste, a specific herbal odor and the formation of uneven porosity of bread and dense crumb. Adding dandelion root powder to the recipe for bread made from wheat flour helps to increase the content of dietary fiber in the finished product by an average of 1.5 times for every 5% of added powder, as well as increasing the content of vitamins B1, B2 and B5. The developed type of bread can be produced at any bakery, as well as public catering enterprise, which will help expand the range of functional food products.